(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The occurrence of the COVID-19 pandemic has caused many people to experience anxiety and difficulties, both because of the impact of decreased body immunity. A few people who suffer from COVID-19 experience stress, changes in concentration, irritability, decreased productivity, interpersonal conflicts, and insomnia. Insomnia can lead to physical and psychological health problems. This psychological health affects insomnia which causes anxiety, depression, and even memory loss. Stress is a form of physical, psychological, emotional, or mental tension that is considered a threat that causes anxiety, depression, social dysfunction and even the intention to end one’s life. The solution to deal with this is by utilizing the clitoria ternatea (butterfly pea). The implementation of this community service was conducted on September 18, 2022 in RW.014, Kelapa Dua Village, Tangerang Regency by provided education about the benefits of clitoria ternatea. Participants in this community service are all housewives in RW.014, Kelapa Dua Village, Tangerang Regency with the aim of providing information about the benefits of clitoria ternatea and improving skills on how to make clitoria ternatea tea. This community service regarding the clitoria ternatea contributes to increasing the knowledge and skills of housewives to apply the making of clitoria ternatea tea drinks. After being educated about the clitoria ternatea and its benefits, housewives became more motivated to made a clitoria ternatea tea drink and apply it for themselves, their families, and some of them inspired to start a home industry business.